EVALUASI PENDAHULUAN POTENSI UNDERGROUND COAL GASIFICATION DI CEKUNGAN SUMATRA SELATAN: STUDI KASUS BATUBARA FORMASI MUARA ENIM: A PRELIMINARY EVALUATION OF UNDERGROUND COAL GASIFICATION POTENTIAL IN THE SOUTH SUMATRA BASIN: A CASE STUDY OF THE MUARA ENIM COAL FORMATION - Dwitama, Eska Putra; Ramdhani, M. Rizki; Ulfa, R. Maria (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2021)
The Underground coal gasification (UCG) is one approach to make use of deep-seated coal by converting it to a more environmentally friendly gas. The South Sumatra Basin is one of Indonesia's productive coal basins. The objective of this study is to find a suitable coal deposit for the development of UCG. Characterizing the coal seams is used to evaluate the potential of Indonesian coal for UCG development in this area. Coal from the Bayung Lencir, Muara Kilis, and Srijaya Makmur areas were evaluated to see if there was any possibility for UCG in these coals. Coal rank, coal thickness, slope and depth of coal seams, the ratio of depth and thickness of coal seam, type of floor and roof rocks and their thickness, hydrogeological conditions (position of coal against aquifers), geological structure, and coal resources were among the parameters evaluated. Based on the parameters of the coal, the evaluation results reveal that Bayung Lincir is suitable area for UCG development.